2012
DOI: 10.1111/j.1468-5906.2012.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Religious Environmentalism: Movement Organizations, Interorganizational Networks, and Collective Action

Abstract: Historically, religious groups have been absent from the American environmental movement, but since the late 1990s a host of new religious environmental movement organizations (REMOs) have emerged. Little is known about REMOs or how religion structures the nascent movement field. Drawing on interviews with leaders of 63 REMOs in the United States, we examined whether theological frames and religious affiliations, on the one hand, and environmental interests, on the other, shaped the formation of information ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Thus, it is no wonder scholars increasingly study movement coalitions. Beamish & Luebbers, 2009;Di Gregorio, 2012;Ellingson, Woodley, & Paik, 2012;Grossman, 2001;Haydu, 2012;Khagram, 2004;Lichterman, 1995;Mix, 2011;Murphy, 2005;Park, 2008;Shaffer, 2000;Stearns & Almeida, 2004 Just as a full understanding of social movement activity requires that we study individual participation in collective action and the role of organizations in mobilization, so too do we need to study the origins and dynamics of organizational collaboration. For example, because frames are often developed through interchanges between coalition partners, failing to examine organizational interaction, including cooperation and conflict, could result in a misspecified explanation of the frame's origin (Croteau & Hicks, 2003;Luna, 2010).…”
mentioning
confidence: 99%
“…Thus, it is no wonder scholars increasingly study movement coalitions. Beamish & Luebbers, 2009;Di Gregorio, 2012;Ellingson, Woodley, & Paik, 2012;Grossman, 2001;Haydu, 2012;Khagram, 2004;Lichterman, 1995;Mix, 2011;Murphy, 2005;Park, 2008;Shaffer, 2000;Stearns & Almeida, 2004 Just as a full understanding of social movement activity requires that we study individual participation in collective action and the role of organizations in mobilization, so too do we need to study the origins and dynamics of organizational collaboration. For example, because frames are often developed through interchanges between coalition partners, failing to examine organizational interaction, including cooperation and conflict, could result in a misspecified explanation of the frame's origin (Croteau & Hicks, 2003;Luna, 2010).…”
mentioning
confidence: 99%
“…Then it provides examples of how religious leaders and activists from Muslim, Catholic, Protestant, Buddhist and Hindu communities are working on a range of initiatives within their respective communities to increase environmental awareness and spark changes in behavior. This pattern of putting movements at the center is followed by many of the research articles on religious environmental social movements (see Veldman et al, 2013;Gottlieb, 2009;Ellingson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This body of literature makes environmental problems rather than environmental spaces a starting point for examining how moral communities form "political movement[s] for adaptive social change" (Jenkins, 2017, p.28). These movements range from adapting to environmental crises (Eucker, 2014;Murphy et al, 2016), local movements of resistance to exploiting natural resources (Witt, 2016;Grim, 1998) and broad-based social movements for changing global policy and practice on environmental protection and care (Gottlieb, 2009;Ellingson et al, 2012;Veldman et al, 2013;Martin-Schramm, 2010). Studies of religious environmental movements reveal strikingly diverse coalitions of religious groups and activists who apply their beliefs into message of care for the environment (Gottlieb, 2009, p.231;Veldman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the authors found that many of these groups see a focus on community building to be an important component of an ethics-based approach (Smith & Pulver, 2009). Through a social network analysis, Ellingson et al (2012) ascertained that REMOs were more likely to collaborate and build alliances with other groups that shared their religious affiliation or theological frame. These researchers also concluded that "REMOs' religious culture shapes the structure of the movement field, which in turn may limit the scope and efficacy of religious environmentalism" (Ellingson et al, 2012, p. 269).…”
Section: Religion and Environmental Changementioning
confidence: 99%